Islamic bank’s performance: a comparative study between Qatar, Bahrain, and Indonesia - Yunice Karina Tumewang; Arief Bachtiar (Proceeding of Conference on Islamic Management, Accounting, and Economics, 2018)
Brief Introduction: Purpose: This study aims to evaluate and compare the performance of Islamic Banks in two different counties complying two different accounting standards, namely Qatar International Islamic Bank (QIIB), Bahrain Islamic Bank (BIB) and Bank Muamalat Indonesia.Design/methodology/approach: This study used quantitative method with secondary data from the annual report of QIIB, BIB, and BMI.Findings: This study sheds light on the financial performance of QIIB, BIB, and BMI as well as the difference among them.Practical implications: The study provides a picture for the Islamic Finance industry regarding the performance of these two banks and what the implication of adopting different accounting standard on this case.Social implications: This study helps to raise the awareness of society about the existence of Islamic banks and how well they have performed.Originality/value: As far as we are concerned, there is only small number of research on finding the significance of accounting standard adoption toward performance of Islamic banks, although the urgency is increasingly growing for a better convergence and significant development of Islamic banks. This work is an attempt to fill in this gap.Keywords: Islamic Banking, Financial Performance, CAMEL ratio